A Review: The Buckling Behavior of Cold-Formed Steel Open Section of Beam - Mat Daud, Siti Suhaiza Fitriah; Jamaluddin, Norwati (Recent Trends in Civil Engineering and Built Environment, 2021)
Cold-formed steel is available in various types of sections depending on their purpose and function in construction industry. Cold-formed steel sections have a very thin thickness as compared to their width. These parts are prone to buckling as a result of this feature. In case of cold-formed steel members, buckling is one of the most critical design criteria to consider. In this research, the aim of study is to investigate the buckling behavior of cold-formed steel section and to review and evaluate the beam strength from the past researches on analytical approach, FEM and standard code. To achieve the objectives of the study, some reviews from the past research about the flexural behaviour that focus on lateral-torsional buckling of open section steel beams and the design strength was made. The three types of the method used had shown the types of buckling modes that appears in the cold-formed steel structure.